Accounting for dissociation and photolysis: A review of the algal toxicity of triclosan. (29th September 2014) - Roberts, Jayne; Price, Oliver R.; Bettles, Nicola; Rendal, Cecilie; van Egmond, Roger
Abstract Triclosan, an antimicrobial agent commonly used in down‐the‐drain consumer products, is toxic to freshwater microalgae. However, the rapid photolysis and pH‐dependent dissociation of this compound may give rise to uncertainty in growth inhibition tests with freshwater microalgae, if these are not well characterized. Methods are presented to minimize these uncertainties by stabilizing pH with an organic buffering agent (Bis‐Tris) and by the application of ultraviolet (UV) covers to remove UV wavelengths. Toxicity tests with these methods were in compliance with the validity criteria of the Organisation for Economic Co‐operation and Development test 201, and no negative effects were seen in controls relative to the unmodified method. The methods were used for toxicity tests with triclosan at pH levels of 7.0, 8.0, and 8.5, yielding effective concentration, 10% values of 0.5 µg/L, 0.6 µg/L, and 12.1 µg/L, respectively. The observed change in toxicity with pH was proportional to the change in bioconcentration factor (BCF) as calculated using the cell model (a dynamic flux model based on the Fick–Nernst–Planck equations, in this case parameterized for an algal cell). Effect concentrations produced with the methods presented in the present study offer robust data on which to base risk assessment, and it is suggested that similar approaches be used to minimize uncertainty when other compounds that dissociate and photolyse are tested. Environ Toxicol Chem 2014;33:2551–2559. © 2014 SETAC